1991
DOI: 10.1093/jn/121.6.832
|View full text |Cite
|
Sign up to set email alerts
|

Large Intestinal pH and Ammonia in Rats: Dietary Fat and Protein Interactions

Abstract: Mature male Sprague-Dawley rats were assigned to a 3 x 3 factorial experiment in which they were fed AIN-76A diets supplying 8, 16 and 32% of energy as protein and 12, 24 and 48% of energy as fat. During the 5 mo of feeding, 10 in vivo measurements of intracolonic pH were recorded on each rat with a flexible electrode. The pH ranged from 7.8 to 8.0 near the anus and declined to 7.4 to 7.5 at 12 cm from the anus. The mean percentages of dry matter in the contents of the colon, divided into three approximately e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(42 citation statements)
references
References 20 publications
3
38
0
Order By: Relevance
“…Similar results were obtained in a subset of experiments by using a miniature glass pH combination electrode with a 0.75-mm-diameter tip and internal reference (MI-415, Microelectrodes). In some experiments, the external reference electrode was anchored subcutaneously in the inguinal region with a suture, without correction for transmucosal potential differences (6 -12 mV) (30), to allow comparison to previous data obtained in the same manner (56). Electrodes were connected to a pH meter (Orion 720A) and calibrated against phosphate pH buffer standards (4.0 -10.0) or [Na Ï© ] standards (0 -100 mM in 20 mM K-acetate).…”
Section: Mucosal Surface Ph and [Namentioning
confidence: 99%
“…Similar results were obtained in a subset of experiments by using a miniature glass pH combination electrode with a 0.75-mm-diameter tip and internal reference (MI-415, Microelectrodes). In some experiments, the external reference electrode was anchored subcutaneously in the inguinal region with a suture, without correction for transmucosal potential differences (6 -12 mV) (30), to allow comparison to previous data obtained in the same manner (56). Electrodes were connected to a pH meter (Orion 720A) and calibrated against phosphate pH buffer standards (4.0 -10.0) or [Na Ï© ] standards (0 -100 mM in 20 mM K-acetate).…”
Section: Mucosal Surface Ph and [Namentioning
confidence: 99%
“…The mammalian colon represents an interesting and important exception. Ammonia is formed in the gut lumen by bacterial action upon nitrogen-containing substances such as urea, and is a major component of colonic lumenal fluid, with concentrations in human and rat fecal dialysates reported to range between 4-70 mM depending upon dietary protein intake (7)(8)(9). Thus, the apical surface of colonocytes is normally bathed by a remarkably high concentration of ammonia.…”
Section: Introductionmentioning
confidence: 99%
“…22) Several studies have reported that the level of NH 3 is approximately 10 mM in rat feces 23) and that an excessive intake of dietary protein by rats also leads to a significant increase in fecal NH 3 . 23,24) Intrarectal administration of NH 2 Cl, which is prepared by the reaction of NH 3 and HOCl, into rats induced intense inflammatory responses in the large intestine, 13) although the concentration of NH 2 Cl used (3.2 mg, 250 mM/0.25 ml, 62.5 ”mol/rat) was much higher than that of chloramines estimated in human phagocytes. 25) Since it has been reported that the concentration of fecal NH 3 in humans is approximately 0.2 mM (mmol/kg), 26) which is similar to that of CH 3 NH 2 in feces, 27) experiments performed using biological levels are needed to further elucidate the possible mechanism(s) of inflammatory re- sponses due to the formation of low-molecular chloramines.…”
Section: Discussionmentioning
confidence: 98%